The quantum mind debate - VV.AA., VV.AA. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
JOSÉ MARÍA GÓMEZ: My question is, the collective excitation of the electron’s spin isstructured in the hydrophobic pockets, exciting these magnons. Demokritov experimenton condensate material and the Bose-Einstein condensate are grouped in better to explainthis with the possibility of the stability, the excitations of magnons in the tubulins? [...].